Alpha/Beta Hydrolase Domain-Containing Protein 2 Regulates the Rhythm of Follicular Maturation and Estrous Stages of the Female Reproductive Cycle - Björkgren, Ida; Chung, Dong Hwa; Mendoza, Sarah; Gabelev-Khasin, Liliya; Petersen, Natalie T.; Modzelewski, Andrew; He, Lin; Lishko, Polina V. (Frontiers in Cell and Developmental Biology, 2021)
Mammalian female fertility is defined by a successful and strictly periodic ovarian cycle, which is under the control of gonadotropins and steroid hormones, particularly progesterone and estrogen. The latter two are produced by the ovaries that are engaged in controlled follicular growth, maturation, and release of the eggs, i.e. ovulation. The steroid hormones regulate ovarian cycles via genomic signaling, by altering gene transcription and protein synthesis. However, despite this well-studied mechanism, steroid hormones can also signal via direct, non-genomic action, by binding to their membrane receptors. Here we show, that the recently discovered membrane progesterone receptor α/β hydrolase domain-containing protein 2 (ABHD2) is highly expressed in mammalian ovaries where the protein plays a novel regulatory role in follicle maturation and the sexual cycle of females. Ablation of Abhd2 caused dysregulation of the estrous cycle rhythm with females showing shortened luteal stages while remaining in the estrus stage for a longer time. Interestingly, the ovaries of Abhd2 knockout (KO) females resemble polycystic ovary morphology with a high number of atretic antral follicles that could be rescued with an injection of gonadotropins. Such a procedure also allowed Abhd2 KO females to ovulate a significantly increased number of mature and fertile eggs in comparison to their wild-type littermates. These results suggest a novel regulatory role of ABHD2 as an important factor in non-genomic steroid regulation of the female reproductive cycle.